Chapter Environmental investigations in the Gulf of Pozzuoli (Naples) in relation to PAHs contamination - Esposito, Mauro (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The Gulf of Pozzuoli (GoP) is a marginal sub-basin of Tyrrhenian Sea, characterized by a strong anthropogenic impact, due to high population density and intense commercial and tourist traffic. Historically, the GoP is dedicated to the farming of bivalve mollusks which are constantly subject to chemical and microbiological monitoring to protect the health of consumers. In the winter season, high levels of PAHs were found in mussels from the Lucrino area. This study reports the environmental analyses and the activities carried out in order to investigate the levels and sources of contamination by PAHs.